Networks and alliances – business schools' answer to mergers and acquisitions?. Issue 10 (11th November 2019) - Pon, Kevin; Duncan, Anne-Laure
Abstract : Purpose: The purpose of this paper is to examine the state of French medium sized business schools in the Grandes Ecole sector of education and how networks and alliances help business schools survive in an ever-changing and global environment. Design/methodology/approach: The material for empirical research for this paper was gathered by using a case study method of four small to medium sized provincial Institutions of Management Education in France. Findings: The paper demonstrates that all of the business schools studied rely on networks and alliances to face globalisation and internationalise their strategy and seems to follow the three typologies of mergers and acquisitions set down by Napier (1989): extension mergers, collaborative mergers and redesign mergers. At present, the networks and alliances are used on a marginal or peripheral way by networking only a part of the institution at one time. Research limitations/implications: Further research at a later date needs to be carried out in order to observe if the pattern will remain or if there may be networks which will start from the core of the institution since the organisations will in the future have more of an international or global culture. Originality/value: The value of this paper is to demonstrate that medium-sized business schools can compensate their limited resources and compete in the global education market. Alliances and networks appear as key ways in achieving goals of sustainability and survival.